The Effect of Digital Banking Adoption, Trust in Fintech, Perceived Security, and Customer Satisfaction on Financial Inclusion in Indonesian Banking - Ridwan, Mohammad; Puspitasari, Ria; Winarsih, Tri; Wangsih, Ingkak Chintya; Sudarmanto, Eko (West Science Business and Management, 2025)
This study investigates the impact of Digital Banking Adoption, Trust in Fintech, Perceived Security, and Customer Satisfaction on Financial Inclusion in Indonesian banking. Employing a quantitative approach, data were collected from 110 respondents using a Likert scale (1–5) and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS) 3. The findings reveal that all four variables significantly and positively influence financial inclusion, with Digital Banking Adoption exerting the strongest impact. The model explains 68% of the variance in Financial Inclusion, underscoring the importance of digital transformation, trust-building, robust security, and customer satisfaction in enhancing financial accessibility. These results provide valuable insights for policymakers and financial institutions to develop targeted strategies that foster financial inclusion in Indonesia.